2002
DOI: 10.1007/bf02708379
|View full text |Cite
|
Sign up to set email alerts
|

Applications of inulin and oligofructose in health and nutrition

Abstract: Inulin and oligofructose belong to a class of carbohydrates known as fructans. The main sources of inulin and oligofructose that are used in the food industry are chicory and Jerusalem artichoke. Inulin and oligofructose are considered as functional food ingredients since they affect the physiological and biochemical processes in rats and human beings, resulting in better health and reduction in the risk of many diseases. Experimental studies have shown their use as bifidogenic agents, stimulating the immune s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
328
2
77

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 525 publications
(428 citation statements)
references
References 86 publications
6
328
2
77
Order By: Relevance
“…A growing body of evidence, however, supports the beneficial effects of fruits and vegetables on bone health (21) . Inulin, for example, a substance abundant in certain plants such as artichokes, has been reported to increase Ca absorption (22) , whereas Ca absorption from low-oxalate vegetables, such as kale and broccoli, appears to be excellent (23) . In the traditional diet of Crete, dairy products are the principal source of dietary Ca, in addition to legumes, vegetables, nuts and small fish.…”
mentioning
confidence: 99%
“…A growing body of evidence, however, supports the beneficial effects of fruits and vegetables on bone health (21) . Inulin, for example, a substance abundant in certain plants such as artichokes, has been reported to increase Ca absorption (22) , whereas Ca absorption from low-oxalate vegetables, such as kale and broccoli, appears to be excellent (23) . In the traditional diet of Crete, dairy products are the principal source of dietary Ca, in addition to legumes, vegetables, nuts and small fish.…”
mentioning
confidence: 99%
“…[2][3][4] The hypolipidemic potential of oligosaccharides as well as probiotics has recently received much attention for these reasons. 5) However, little is known about whether the consumption of indigestible oligosaccharides can affect body fat accumulation.…”
mentioning
confidence: 99%
“…Moreover, both groups treated with of INPs (LD) and INPs (HD) plus SIL were comparable to the control and these treatments improved the lipid profile levels and the antioxidant enzymes activity. In this concern, Kaur and Gupta, (2002) reported that inulin contains oligofructose which inhibits fatty acid synthesis and has a prebiotic effect and decrease total lipids, triglyceride, LDL and cholesterol through the inhibition of hydroxyl methyl glutaryl-CoA reductase (Brosnahan and Fraer, 2009), but it increased HDL, total protein and albumin. Moreover, it was reported that inulin showed antioxidant properties, increased the activity of antioxidant enzymes (Atta et al, 2010) and has a free radical scavenging activity (Hassan and Yousef, 2010).…”
Section: Discussionmentioning
confidence: 99%